Imagining the Global Transnational Media and Popular Culture Beyond East and West - Darling-Wolf, Fabienne (New Media World, 2015)
Based on a series of case studies of globally distributed media and their reception in different parts of the world, Imagining the Global reflects on what contemporary global culture can teach us about transnational cultural dynamics in the 21st century. A focused multisited cultural analysis that reflects on the symbiotic relationship between the local, the national, and the global, it also explores how individuals' consumption of global media shapes their imagination of both faraway places and their own local lives. Chosen for their continuing influence, historical relationships, and different geopolitical positions, the case sites of France, Japan, and the United States provide opportunities to move beyond common dichotomies between East and West, or United States and "the rest." From a theoretical point of view, Imagining the Global endeavors to answer the question of how one locale can help us understand another locale. Drawing from a wealth of primary sources-several years of fieldwork; extensive participant observation; more than 80 formal interviews with some 160 media consumers (and occasionally producers) in France, Japan, and the United States; and analyses of media in different languages-author Fabienne Darling-Wolf considers how global culture intersects with other significant identity factors, including gender, race, class, and geography. Imagining the Global investigates who gets to participate in and who gets excluded from global media representation, as well as how and why the distinction matters.